1994
DOI: 10.1038/hdy.1994.76
|View full text |Cite
|
Sign up to set email alerts
|

Linkage studies in Mytilus edulis, the mussel

Abstract: Electrophoretic data at 10 allozyme loci from the offspring of six single pair matings of Mytitus edulis were analysed for linkage. Significant deviations from expected octopine dehydrogenase (Odh)/phosphoglycerate kinase (Pgk) and leucine aminopeptidase (Lap )/esterase D (EsD) di-locus genotype frequencies were evident in two families. In the former case, the recombination frequency was 0.463 suggesting epistasis but in the latter case a recombination frequency of 0.022 indicated almost complete linkage betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…Since larvae or newly settled zebra mussels were not analysed in our study, we are unable to test the model. There is the possibility that the three loci, EST‐D , GPI and OPDH at which the majority of significant F IS values were observed, form part of a 5‐locus linkage group ( GPI, OPDH, LAP, EST‐D and MPI ) as reported for the marine mussel, Mytilus edulis (Beaumont, 1994) and that selection acts against heterozygotes at the linked loci. However, this must be discounted since there was no evidence for significant linkage disequilibrium between any locus pair.…”
Section: Discussionmentioning
confidence: 97%
“…Since larvae or newly settled zebra mussels were not analysed in our study, we are unable to test the model. There is the possibility that the three loci, EST‐D , GPI and OPDH at which the majority of significant F IS values were observed, form part of a 5‐locus linkage group ( GPI, OPDH, LAP, EST‐D and MPI ) as reported for the marine mussel, Mytilus edulis (Beaumont, 1994) and that selection acts against heterozygotes at the linked loci. However, this must be discounted since there was no evidence for significant linkage disequilibrium between any locus pair.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, Väinö lä and Hvilsom (1991) described concordant clines for four diagnostic allozymes across a relatively narrow transition zone of 100 km along the Øresund region. Subsequent work has shown that these loci do not segregate independently because they belong to the same linkage group (Beaumont, 1994). Nonetheless, it remains possible that stochastic influences (genetic drift) probably interact with one or more deterministic forces specific to these diagnostic loci to produce concordant clines for these markers and in dissociating the position and width of these clines from others (Barton, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…None of these explanations can fully explain the observations. Beaumont (1994) showed that PGM* and PGI* are not linked in M. edulis. Non-linkage of these two loci was also observed in mussels by Gardner et al (1996), and thus the two loci PGI* and PGM* make independent contributions to the identification of different groups of blue mussels.…”
Section: Discussionmentioning
confidence: 99%